If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x * x + 6x + c = 0 Multiply x * x x2 + 6x + c = 0 Reorder the terms: c + 6x + x2 = 0 Solving c + 6x + x2 = 0 Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Add '-6x' to each side of the equation. c + 6x + -6x + x2 = 0 + -6x Combine like terms: 6x + -6x = 0 c + 0 + x2 = 0 + -6x c + x2 = 0 + -6x Remove the zero: c + x2 = -6x Add '-1x2' to each side of the equation. c + x2 + -1x2 = -6x + -1x2 Combine like terms: x2 + -1x2 = 0 c + 0 = -6x + -1x2 c = -6x + -1x2 Simplifying c = -6x + -1x2
| 6y^2+11=4y | | 10/15x=8 | | X/8=x+3/20 | | 5+2n=31 | | m^2-54=3m | | 3-3x=5x-85 | | 20/10x | | 4x^3-5x+5=0 | | y^2=14-5y | | x=14+3 | | 6x+9=7x+5 | | -2a(a+3)= | | 3x-12x+1=6x+3-15+4 | | (2x^3)(-4x^6)(3x^2)= | | x-12x+1=2x+1-15x+4 | | Y+6x=6 | | 3x+78=67 | | 2x+4=3x+0 | | 14-4x=-2x-6 | | 22/7= | | 10w/4w^2 | | 3(5)+5x=-15 | | 1018.395/16.5+5= | | (x-3)(x-3)=10 | | 0=16t^2+32t | | 3y+5(-3)=-15 | | G(2)=3t-7 | | 8(2+2)=4(2+1)-20 | | 9t+14-5t-7=29 | | m^2-30=7m | | 10x^2-12x-9=0 | | w/x=y/z |